THE IMPACT OF LAZISMU DIY'S PRODUCTIVE ZAKAT ON POVERTY REDUCTION IN YOGYAKARTA - Sutrisno; Mukhlis Rahmanto (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This study examines the implementation of the productive zakat program by the LAZISMU DIY zakat institution in Yogyakarta, as well as the impacts and obstacles encountered in its implementation. A qualitative approach was used by interviewing three zakat administrators and five zakat recipients to support the community through programs that include food carts, capital provision, and economic empowerment of grocery stores and traditional snacks. LAZISMU Yogyakarta has created a poverty alleviation program and sustainable assistance through several economic empowerment programs. The results of the study concluded that the programs implemented by LAZISMU have a positive impact on improving the welfare of poor recipients of productive zakat assistance with four main poverty alleviation programs. In general, the average increase in income after receiving productive zakat funds from LAZISMU DIY. There are challenges faced by mustahik, namely limited resources in managing their businesses. This study recommends the need for increased guidance for mustahik in business management by involving experienced professionals and collaborating with new muzakki to optimize funding for sustainable poverty alleviation programs.